Impella flow pump reinsertion after axillary graft thrombectomy: Technical points in replacing axillary Impella. (July 2021) - Haddad, Osama; Jacob, Samuel; Ung, Ryan L; Goswami, Rohan M; Patel, Parag C; Pham, Si M; Sareyyupoglu, Basar
Axillary Impella devices are increasingly employed for long-term support of patients with systolic heart failure and shock. Axillary access allows for awake support and ambulation, which carries an inherent risk of disconnection or malposition. We report a series of two cases where device replacement due to dysfunction and malposition can be completed safely through the original axillary graft using axillary graft thrombectomy, given that the clot burden could be a major source of morbidity to the patient.